Cinnamon essential oil synergizes with sodium hypochlorite to suppress VBNC formation in Escherichia coli O157:H7 by modulating the temporal expression of arcA/relA-associated stress regulators - Haoqing Zhao; Zongwei Bai; Jingfeng Zhang; Yamei Chen; Huiting Huang; Xiaoxuan Wang; Jiawen Sun; Lei Shi; Xiaoli Xu; Lichao Zhao (Food Microbiology, 2027)

The toxicity of petroleum pollutants on marine zooplankton: Multiscale effects from individuals to populations - Tianrui Liu; Xiahui Liu; Wangguangming Yu; Jingfeng Bai; Wei Shen; Xuan Wu (Marine Pollution Bulletin, 2026)

Carbon/nitrogen composite induction of extracellular polymeric substances from Desulfovibrio desulfuricans enables Cu2S quantum dot biosynthesis - Guangwen Zheng; Weifeng Song; Zuoyi Yang; Yantong Gao; Qian Yin; Ziheng Song; Chuanying Tu; Keqin Zhou; Junming Bian; Jingfeng Peng; Xiangdan Zhang; Xiaoyan Bai (Journal of Environmental Chemical Engineering, 2026)

Dual regulation of EPS protein structure by C/S composite induction enables controlled biosynthesis of ZnS quantum dots - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Yantong Gao; Qian Yin; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2026)

Unvegetated corridors nonlinearly regulate hydrological connectivity and sediment delivery in a microtidal marsh - Dawei Wang; Junhong Bai; Ken Schoutens; Jingfeng Wang; Wei Wang; Chuanhui Gu (CATENA, 2026)

Asynchronous alterations in bacterial composition and function increased functional redundancy related to greenhouse gas emissions following coastal habitat transitions - Jichen Qiu; Junhong Bai; Di Wang; Yuhao Xu; Yue Liu; Yujia Zhai; Jingfeng Wang; Changhong Xiao; Langying Long; Huihua Lyu; Mengwei Chu (Marine Pollution Bulletin, 2026)

Bio-electrochemical regulation of sulfur transformations for boosted sulfur-based denitrification and integrated sulfate abatement: Performance and mechanisms - Jingfeng Ding; Gaoming Wu; Dazhi Bai; Bin Yang; Yang Hou; Lecheng Lei; Zhongjian Li (Journal of Environmental Chemical Engineering, 2026)

Habitat changes induced by converting coastal aquaculture to wetlands enhance taxonomic diversity and cross-species interaction strength of macro- and meiobenthos - Jichen Qiu; Wenjing Cao; Zhaohan Zhang; Junhong Bai; Liangxing Cao; Yuhao Xu; Jiajie Mei; Yaqi Wang; Yue Liu; Jingfeng Wang; Yanan Zhang (Aquaculture, 2026)

Nano/microplastics induce distinct reed growthdefense tradeoff via hormone signal transduction and carbohydrate metabolism - Yaqi Wang; Junhong Bai; Yujia Zhai; Xiaoman Jiang; Jichen Qiu; Ling Zhang; Jingfeng Wang; Willie Peijnenburg; Martina G. Vijver (Journal of Hazardous Materials, 2026)

Impact of large-scale climate indices on total nitrogen concentrations in drinking water sources cannot be overlooked - Ning Li; Jingfeng Xiao; Zheng Zhang; Rui Bai; Jiayi Yong; Ziyu Ning; Miao Chen; Yaxiong Chen; Shuli Xin; Shengwu Xiong (Journal of Hydrology, 2025)

C/S composite induction on spatial structure of EPS from Desulfovibrio desulfuricans subsp. and their adsorption performance of Zn(II) - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2025)

Impacts of meteorological drought on peak vegetation productivity of grasslands from perspectives of canopy structure and leaf physiology - Wenrui Bai; Huanjiong Wang; Jingfeng Xiao; Xing Li; Quansheng Ge (International Journal of Biometeorology, 2025)

Aflatoxin B1-induced early developmental hepatotoxicity in larvae zebrafish - Chi Feng; Hongxia Bai; Xu Chang; Zhixuan Wu; Wu Dong; Qianqian Ma; Jingfeng Yang (Chemosphere, 2023)

Surface modification to enhance the decarbonization performance of coal-series kaolin by triboelectric separation - Jingfeng He; Xin Zhang; Qiang Bai; Shibo Huang; Hao Chen; Chengjing Guo; Lingtao Zhu; Bin Yang (Applied Clay Science, 2023)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Skin transcriptome, tissue distribution of mucin genes and discovery of simple sequence repeats in crucian carp ( Carassius auratus ) - Jie Bai; Xiucai Hu; Aijun Lü; Ruixia Wang; Rongrong Liu; Jingfeng Sun; Yuchen Niu (Journal of Fish Biology, 2020)
Crucian carp ( Carassius auratus ) is one of the major freshwater species and important food fish in China. Fish skin acts as the first line of defence against pathogens, yet its molecular and immune mechanism remains unclear. In this study, a de novo transcriptome assembly of C. auratus skin was performed with the Illumina Hiseq 2000 platform. A total of 49,154,776 clean reads were assembled, among which 60,824 (46.86%), 37,103 (28.59%), 43,269 (33.33%) unigenes were annotated against National Center for Biotechnology Information, Gene Onotology and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, respectively. KEGG Orthology categories were significantly involved in immune system (20.50%), signal transduction (18.04%) and mucosal mucin genes ( e.g. , muc2 , muc5AC , muc5B , muc17 , muc18 ). The high expression of muc18 gene was observed in brain; that of muc2 in intestine; and that of muc5AC in skin, liver, spleen, intestine and muscle. Moreover, the potential 28,928 simple sequence repeats with the three most abundant dinucleotide repeat motifs (AC/GT, AG/CT, AT/AT) were detected in C. auratus . To authors’ knowledge, this is the first report to describe the transcriptome analysis of C. auratus skin, and the outcome of this study contributed to the understanding of mucosal immune response of the skin and molecular markers in cyprinid species.

Detection and characterization of Aeromonas salmonicida subsp. salmonicida infection in crucian carp Carassius auratus - Zhengyi Lian; Jie Bai; Xiucai Hu; Aijun Lü; Jingfeng Sun; Yongjun Guo; Yajiao Song (Veterinary Research Communications, 2020)